Morphological analysis of collagen and elastic fibers in oral squamous cell carcinoma using special stains and comparison with Broder's and Bryne's grading systems - Rinju Elsa John; Sarvani Murthy (Wolters Kluwer Medknow Publications, 2016)
Objectives: Morphologic detection of connective tissue fiber changes in oral squamous cell carcinoma (OSCC) using special stains remains less documented. The aims of the present study were to study the collagen and elastic fibers in different stages of OSCC and to correlate these changes with two grading systems - Broder's and Bryne's. Study Design: Forty-eight cases of OSCC were studied using hematoxylin and eosin, Verhoeff's - Van Gieson stain for elastic fibers and picrosirius red stain for collagen fibers. The changes were compared with all the grades of carcinoma. Normal mucosa was taken as control. Results: Statistical analysis using Chi-square and ANOVA, showed significant association between the grades of carcinoma and extracellular matrix changes. Greenish-yellow collagen fibers were found to be significantly increased in the poorly differentiated/Grade 3 cases (P< 0.0001) where as well-differentiated/Grade 1 cases showed predominantly reddish-orange and yellowish-orange birefringence of collagen fibers. Chi-square analysis showed a significant amount of fragmented pattern of elastic fibers in poorly differentiated OSCC (χ2 = 104.45, P = 0.009)/Grade 3 OSCC (χ2 = 94.81, P = 0.016). Conclusion: The study of the connective tissue stromal changes can be used as an adjunct to histological grading and thereby helping the surgeon to determine the amount of marginal clearance.